THE PRINCIPAL’S ROLE IN IMPLEMENTING DIGITAL LITERACY IN SCHOOL - Nailufar, Rifa; Imaddudin, Salman; Muttaqin, Rudli Zamal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The principal as the leader of the education unit has an important role in realizing a school atmosphere that is in accordance with the needs of the times where digital literacy is an inseparable thing. This research reveals how the role of principals in creating a culture of digital literacy in schools. The method used in this study is a descriptive method with a qualitative approach, where data collection is carried out through a process of interviews, observations and documentation studies. Interviews were conducted with the principal, teachers and parents of the students. The data obtained are then grouped and analyzed until the final conclusion of the study is drawn. Interviews were conducted with the principal, teachers and parents of the students. The data obtained are then grouped and analyzed until the final conclusion of the study is drawn. This research reveals how 3 indicators of digital literacy in schools, namely: class-based indicators, school culture-based indicators, and community-based indicators are met in ALIES and how the role of the principal in supporting the digital literacy movement. The results of the study revealed that the principal's digital literacy is quite good which is described through the ability to use technology and digital information implemented in carrying out their duties. The role of the principal in building an atmosphere of digital literacy is illustrated through his function as an educator, manager, administrator, supervisor, leader, innovator and motivator. Digital literacy is a skill that must be possessed by all education stakeholders in order to achieve educational goals, therefore the principal needs to maximize his leadership role in realizing a digital literacy culture in schools by making various innovations that are adapted to the conditions of each school.